Are 3D tumor cell spheroids a utile system for the in vitro evaluation of diagnostic radiotracers? - Judmann, Benedikt; Keller, Florian; Wängler, Björn; Schirrmacher, Ralf; Rudolf, Rüdiger; Wängler, Carmen (ACS omega, 2024)
By possibly bridging the gap between 2D in vitro cell assays and in vivo applications, tumor cell spheroid cultures offer promising avenues for advancing innovation in nuclear medicine. Regarding the in vitro evaluation of therapeutic radioligands, tumor cell spheroids have been successfully used to assess the therapeutic efficacy against human tumors. However, studies employing spheroids for testing diagnostic tracers are missing. The present work investigated the receptor interaction of a diagnostic radioligand with different tumor cell spheroids and compared the results to those received from a standard 2D cell assay to validate the usefulness of 3D cell systems for diagnostic radiotracer testing. For this purpose, a new agent─[68Ga]Ga-NODAGA-PEG5-c(RGDfK)─was developed. In competitive displacement assays against [125I]I-echistatin in human U87MG glioblastoma cell monolayers, NODAGA-PEG5-c(RGDfK) demonstrated specific binding and IC50 values of 3.08 ± 0.12 and 10.39 ± 0.89 μM in the absence and presence of basal membrane extract (BME), respectively. Compared to cell monolayers, the 3D cell aggregates yielded considerably higher IC50 values of 16.46 ± 2.88, 20.52 ± 4.41, and 18.44 ± 6.06 μM in spheroids generated without additive, collagen-1, and BME supplementation and showed considerable unspecific binding. The obtained data were contextualized by investigating differences in morphology, cell viability, and integrin content per cell of the 2D and 3D cell models as well as the influence of ECM composition. Integrin expression per cell was stable, while spheroid density and the associated radioligand uptake were varying, depending on the culture conditions. This suggests a correlation between the NODAGA-PEG5-c(RGDfK)-integrin αvβ3-interaction and cell model compactness. Further, a considerable influence of matrix components on ligand-receptor interaction could be demonstrated. Overall, the results showed profound differences between the 2D and 3D radiotracer assays investigated, and further work is warranted to verify the expected added value of 3D tumor cell spheroids for the evaluation of diagnostic radioligands.
Gesehen am 10.04.2025